Initial experience with the coaxial dual-lumen Scepter C balloon catheter for endovascular management of cerebral vasospasm from subarachnoid hemorrhage. (31st January 2013) - John, Seby; Spiotta, Alejandro M; Turner, Raymond M; Chaudry, M Imran; Turk, Aquilla S; Hui, Ferdinand
Abstract : Background: Post-hemorrhagic cerebral vasospasm accounts for significant morbidity and mortality in patients with subarachnoid hemorrhage (SAH). Intra-arterial therapies including vasodilator administration and/or balloon angioplasty are used when medical management fails. The Scepter C is a newer dual coaxial lumen temporary occlusion balloon catheter used for the treatment of post-hemorrhagic cerebral vasospasm. Objective: To report our early experience with the use of Scepter C for the treatment of post-hemorrhagic cerebral vasospasm. Methods: We reviewed cases from two institutions where the Scepter C balloon catheter was used for the treatment of cerebral vasospasm related to SAH. Results: Seven patients were identified who underwent endovascular treatment with the Scepter C balloon catheter for treatment of SAH-related cerebral vasospasm. All patients had cerebral vasospasm that was refractory to medical management and it was technically feasible to use the catheter for this indication. Compared with larger double-lumen catheters, the Scepter C catheter was more trackable given the presence of a more steerable microwire. There were no complications or large vessel vasospasm recurrence after the procedure requiring repeat intra-arterial therapy. Conclusions: Endovascular treatment for post-hemorrhagic cerebral vasospasm is used when medical management fails or because of complications of medical therapies. With continuing advancements in the development of endovascular devices and techniques, more options are available for the management of cerebral vasospasm. Our initial experience with the dual coaxial lumen Scepter C occlusion balloon catheter demonstrates its feasibility in the treatment of cerebral vasospasm.